A Comparative Study on the Readiness Parameters of Highway Construction Projects - Nur Afiqah, Mohd Radzi; R. A., Rahman; Doh, Shu Ing; M., Esa (IOP Science, 2021)
Successful highway projects could help contribute to a country's economic development and growth. One of the factors that cause delays in highway projects is starting too early (i.e., premature start), and assessing the readiness of the project before construction could prevent it from happening. However, different types of highway projects can have various causes of delay. Therefore, having inappropriate readiness parameters can impair the process of assessing construction readiness. This study aims to compare the construction readiness parameters (CRPs) between different types of highway projects. To achieve that objective, questionnaire survey data from 105 industry practitioners with highway construction working experiences is analyzed using the analysis of variance (ANOVA), descriptive statistics, and mean score ranking technique. The results reveal 32 CRPs that are critical for both highway and expressway projects. Also, there are 6 CRPs that are only critical for highway projects. This study contributes to the current body of knowledge by illustrating any discrepancies of the readiness parameters between types of highway projects. The lessons from this study could help the industry to justify the usage of the parameters for assessing their highway projects in preventing premature starts.